Centipeda minima (Ebushicao) extract inhibits PI3K-Akt-mTOR signaling in nasopharyngeal carcinoma CNE-1 cells - Guo, Yu-qing (Chin Med, 2015)
BACKGROUND: Centipeda minima (Ebushicao) has been used for the treatment of various diseases, such as nasal allergies, rhinitis and sinusitis, nasopharyngeal carcinoma, cough, and headache. This study aims to investigate the anticancer activities of Centipeda minima ethanol extracts (CME) against nasopharyngeal carcinoma cell CNE-1 and their underlying mechanism. METHODS: CNE-1 cells were treated with different concentrations (15–50 μg/mL) of CME for different time intervals (24, 48, and 72 h). Cytotoxicity of CME was determined by MTT assay. Cell morphological changes were observed by fluorescence microscopy after HO 33258 staining. Cell cycle status was evaluated by flow cytometry following propidium iodide staining. Apoptosis was detected by flow cytometry following annexin V-FITC/PI staining. The levels of apoptosis-associated and PI3K-Akt-mTOR signaling related proteins were measured by western blotting analysis. RESULTS: CME (15–50 μg/mL) significantly inhibited the proliferation of CNE-1 in a dose- and time-dependent manner (P = 0.026 for 15 μg/mL, P < 0.001 for 25, 30, 40, and 50 μg/mL, respectively); the IC(50) values (μg/mL) were 41.57 ± 0.17, 30.34 ± 0.06 and 24.98 ± 0.08 for 24, 48 and 72 h treatments, respectively. Significant morphological changes of CNE-1 cells displaying apoptosis were observed after CME treatment. CME showed low cytotoxicity toward normal LO2 cells. CNE-1 cells were arrested in the G2/M phase while treated with 15, 25, 40 μg/mL of CME, respectively (P = 0.032, P = 0.0053, P < 0.001). CME (15, 25, 40 μg/mL) down-regulated Bcl-2 expression (P = 0.032, P = 0.0074, P < 0.001), and up-regulated Bax (P = 0.026, P = 0.0056, P < 0.001) with activation of caspase-3, caspase-8, caspase-9, and PARP observed in CNE-1 cells (P = 0.015, P = 0.0067, P < 0.001 for caspase 3; P = 0.210, 0.028, < 0.001 for caspase 8; P = 0.152, 0.082, 0.0080 for caspase 9; P = 0.265, 0.0072, < 0.001 for PARP). CME suppressed the activation of the PI3K-AKT-mTOR pathway (P = 0.03, 0.0007, 0.004, 0.006, 0.022 for p-PI3K, p-Akt-Ser(473), p-Akt-Thr(308), p-mTOR-Ser(2448), p-mTOR-Ser(2481), respectively after 40 μg/mL of CME treated for 24 h). CONCLUSION: CME inhibited the proliferation of CNE-1 cells and activation of the PI3K-AKT-mTOR signaling pathway.